2015
DOI: 10.3892/etm.2015.2533
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of a case of acute myocardial infarction due to type A aortic dissection by coronary artery stenting: A case report

Abstract: Acute type A aortic dissection (AD) has been recognized as a potentially life threatening condition, which sometimes involves the ostium of the coronary artery and may lead to acute myocardial infarction (AMI). In patients with acute type A AD presenting with clinical signs of AMI, it is crucial to establish the diagnosis rapidly in order to proceed with the correct treatment. The present study reports the diagnosis of a rare case of acute type A AD with the typical presentation of acute inferior MI and cardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Routine coronary angiography in these patients is still controversial. In the studies performed, no significant difference was found between the patients who underwent preoperative coronary angiography and those who did not undergo mortality, length of stay and discharge 6 . Surgical techniques such as Bentall, David or Cabrol can be applied depending on the involvement of the aortic valve and the distance of the flap to the coronary ostium 7 .…”
Section: Discussionmentioning
confidence: 86%
“…Routine coronary angiography in these patients is still controversial. In the studies performed, no significant difference was found between the patients who underwent preoperative coronary angiography and those who did not undergo mortality, length of stay and discharge 6 . Surgical techniques such as Bentall, David or Cabrol can be applied depending on the involvement of the aortic valve and the distance of the flap to the coronary ostium 7 .…”
Section: Discussionmentioning
confidence: 86%
“…This can be considered another safe answer in similar situations. Wang et al presented a case with successful treatment of acute myocardial infarction due to type A aortic dissection by right coronary artery stenting [Wang 2015]. Thus, given the unstable hemodynamic condition, due overt myocardial ischemia, reestablishing blood flow by cardiac catheterization stenting also is reasonable.…”
Section: Discussionmentioning
confidence: 99%